EFEITOS DO TREINAMENTO FÍSICO COMBINADO NA MODULAÇÃO AUTONÔMICA CARDIOVASCULAR DE RATAS SUBMETIDAS A SOBRECARGA DE FRUTOSE - PEREIRA, Rafael Durans (2022)
Excessive intake of fructose chronically can lead to the development of chronic diseases that associated lead the individual to a clinical picture of metabolic syndrome. Physical exercise has been increasingly recommended as a form of prevention and treatment of non-communicable chronic diseases. Considering the effects of excessive fructose consumption, the objective of this study was to verify the effects of combined physical training on cardiovascular autonomic modulation in rats submitted to fructose overload. For that, 24 Wistar rats were divided into three groups, namely control (GC), sedentary fructose (GF) and combined (GTC). The animals of the GF and GTC groups received 100g/L of fructose in the drinking water. All animals underwent an aerobic capacity and strength test to calculate load and training speed, after which the GTC started training (8 weeks, 5x/week, 1 hr/day). At the end of the protocol, the rats underwent carotid artery cannulation surgery to acquire biological signals to assess autonomic modulation through HR variability in the time (DT) and frequency (DF) domains. Therefore, an increase inthe VAR-IP (74.50 ± 7.21ms) and RMSSD (4.23±0.49ms²) of the GTC was observed in the DT when compared with GF and in the DF a higher HF (33.83±2.64 %) and lower LF (4.90±1.20%). As for the variability of blood pressure, the GTC had the lowest VAR SBP (17.50±6.92 mmHg), lowest LF SBP (2.44±0.58mmHg) and alpha index (1.44±0.05 ms/mmHg ). Therefore, combined physical training is able to improve cardiovascular autonomic modulation in rats subjected to fructoseoverload.